Enhancing Near‐Room‐Temperature Thermoelectric Performance of n‐Type Mg3(Bi,Sb)2‐Based Materials through Induction Sintering and Mg Evaporation Control - Yang, Jiawei; Zhao, Shuang; Liu, Xinyu; Chen, Ling; Wu, Li‐Ming (Advanced functional materials, 2025)
n‐type Mg3(Bi,Sb)2 is a newly developed high‐performance thermoelectric material with significant potential for use in next‐generation thermoelectric coolers (TECs) at room temperature. However, its electrical transport properties, sensitive to magnesium content and high vapor pressure, pose challenges for manufacturing. Herein, using the finite element method, it is demonstrated that reducing the effective specific surface area suppresses magnesium evaporation. Increasing the thickness of the Mg3(Bi,Sb)2 pellet (φ = 12.7 mm) from 3 to 10 mm reduces evaporation by approximately 60%. Building on this, an induction sintering technique is employed, which extends sintering time at 1053 K, enabling the successful preparation of n‐type 0.25%‐Te‐doped Mg3(Bi,Sb)2 material. The as‐obtained Mg3.2Bi1.4975Sb0.5Te0.0025 material exhibits a thermoelectric figure of merit (zT) value of approximately 0.83 at room temperature, attributed to a 20‐fold increase in Hall mobility to lattice thermal conductivity ratio. The homemade seven‐pair module of n‐type Mg3(Bi,Sb)2 and commercial p‐type Bi2Te3 achieves a maximum temperature difference of 63.4 K at room temperature, one of the highest reported. These results reaffirm the superior performance of n‐type Mg3(Bi,Sb)2 and propose an economical approach to scalable production. Reducing specific surface area effectively reduces Mg evaporation, leading to n‐type Mg3(Bi, Sb)2 material (i.e., Mg3.2Bi1.4975Sb0.5Te0.0025) with a noteworthy room‐temperature figure of merit of approximately 0.83. The homemade seven‐pair TEC module, comprised of the as‐obtained n‐type Mg3(Bi,Sb)2 and commercial p‐type Bi2Te3, experimentally achieves a ΔTmax = 63.4 K at a hot‐side temperature of room temperature.